Toward Integrated Processual Theories of Crime: Assessing the Developmental Effects of Executive Function, Self-Control, and Decision-Making on Offending - Altikriti, Sultan (Criminal justice and behavior, 2021)
Research on executive function indicates that self-control stems partially from normative brain development. Extant research has also provided evidence of an association between self-control and offender decision-making. Yet, to date, there has been no attempt to account for these associations within one model. The current study used structural equation modeling to estimate the links between executive function, self-control, moral disengagement, and perceptions of risk and reward in a sample of male offenders (n = 1,170) from the Pathways to Desistance data. The results indicated that executive function affects self-control, which subsequently influences perceptions of offending and offending behavior, supporting the integration of these concepts under one processual model. Moreover, moral disengagement, certainty of punishment, and rewards of offending mediated the majority of the effects of self-control on offending. The results from the current study advance theories in the life-course/developmental perspective and inform policy toward a developmentally oriented juvenile justice system.